Fuzzy Information Modeling in a Database System - Salam Ismaeel; Ayman Al-Khazraji; Karama Al-delimi (IAES International Journal of Artificial Intelligence (IJ-AI), 2017)
A Fuzzy logic (FL) provides a remarkably simple way to draw definite conclusions from vague, ambiguous or imprecise information. In a sense, fuzzy logic resembles human decision making with its ability to work from approximate data and find precise solutions. In this paper a fuzzy information modeling system was developed then used in a database, which contains fuzzy data and real data, to create new information assistance capable of making any decision about this data. The proposed system is implemented on a special database used to evaluation workers or users in any formal organizations.